A fully integrated whole-head helium OPM MEG: a performance assessment compared to cryogenic MEG - Bonnet, Maxime; Schwartz, Denis; Gutteling, Tjerk; Daligault, Sebastien; Labyt, Etienne (Frontiers in Medical Technology, 2025)
Magnetoencephalography (MEG) is a neuroimaging technique that measures neuronal activity at a millisecond scale. A few years ago, a new generation of MEG sensors emerged: optically pumped magnetometers (OPMs). The most common OPMs use alkali atoms as the sensing element. These alkali OPM sensors must be heated to approximately 150°C, in contrast to classical MEG sensors [superconducting quantum interference device MEG], which need to be cooled down to −269°C. This article focuses on a new kind of OPM that uses Helium-4 gas as the sensing element, which solves some disadvantages of alkali OPMs. 4He-OPM sensors operate at room temperature, with negligible heat dissipation (10 mW) and thus do not need thermal insulation. They also offer a large dynamic range (±200 nT) and frequency bandwidth (2,000 Hz). The main goal of this study is to characterize the performance of a whole-head MEG system based on 4He OPM sensors (4He OPM MEG). We first simulated different sensor configurations with three different numbers of channels and three different head sizes, from child to adult, in order to assess the signal-to-noise ratio and the source reconstruction accuracy. Experimental testing was also performed using a phantom to simulate brain magnetic activity. The simulation and experiments show equivalent detection capability and localization accuracy on both MEG systems. These results illustrate the benefit of 4He OPM sensors that operate at room temperature and are positioned closer to the scalp.